In-state tuition for undocumented immigrants and its impact on college enrollment, tuition costs, student financial aid, and indebtedness - Catalina Amuedo-Dorantes; Chad Sparber (Institute for the Study of Labor (IZA), 2012)
The 1996 Immigration Reform and Responsibility Act barred states from giving unlawful residents postsecondary education benefits that states do not offer to U.S. citizens. In contrast to this federal law, several states have passed legislation explicitly allowing undocumented immigrants to pay in-state tuition rates. We use a difference-in-difference estimation methodology to assess intended and unintended consequences of this tuition policy. First, we find evidence consistent with past studies that postsecondary enrollment rates of Hispanic non-citizens have increased in treatment states relative to control states without negatively impacting the enrollment rates of native-born Americans. Second, state policies benefiting undocumented immigrants have not increased tuition and fees at comprehensive and community colleges attended by the vast majority of students, though rates have risen at flagship universities. Finally, despite some weak association with increased indebtedness among Hispanic natives, resident tuition subsidies for undocumented immigrants do not appear to have reduced financial aid or increased indebtedness for other demographic groups.
Keywords: F22; J15; I23; I28; 330; immigration; college tuition; DREAM Act; Einwanderung; Hispano-Amerikaner; Studienfinanzierung; Wirkungsanalyse; Hochschule; Schulbesuch; Private Verschuldung; USA